1997
DOI: 10.1104/pp.113.2.367
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Characterization, and Structural Analysis of a Plant Low-Temperature-Induced Protein

Abstract: We have purified to near homogeneity a recombinant form of the protein BN28 (rBN28), expressed in response to low temperature in Brassica napus plants, and we have determined its solution structure. Antibodies raised against rBN28 were used to characterize the recombinant and native proteins. Similar to many other lowtemperature-induced proteins, BN28 is extremely hydrophilic, such that it remains soluble following boiling. lmmunoblot analysis of subcellular fractions indicated that BN28 was not strongly assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 45 publications
2
11
0
1
Order By: Relevance
“…Other workers have observed that apparently unfolded LEA (or similar) proteins become more structured when water activity is decreased by e.g. trifluoroethanol (56,58,66), high salt concentration (54), or drying in the presence of sucrose (67). This has obvious physiological relevance in desiccation-tolerant systems, including the anhydrobiotic nematode A. avenae, but leads to the further question of what the functions of the folded, presumably partially dehydrated, LEA proteins might be.…”
Section: Discussionmentioning
confidence: 99%
“…Other workers have observed that apparently unfolded LEA (or similar) proteins become more structured when water activity is decreased by e.g. trifluoroethanol (56,58,66), high salt concentration (54), or drying in the presence of sucrose (67). This has obvious physiological relevance in desiccation-tolerant systems, including the anhydrobiotic nematode A. avenae, but leads to the further question of what the functions of the folded, presumably partially dehydrated, LEA proteins might be.…”
Section: Discussionmentioning
confidence: 99%
“…B, Levels of the B. napus BN28 protein in nonacclimated (NA) and cold-acclimated (CA) control and CBF-expressing transgenic B. napus plants. Total soluble protein (100 g) prepared from nonacclimated and 3-week coldacclimated plants was subjected to immunoblot analysis using antiserum raised to the BN28 polypeptide (Boothe et al, 1997). Numbers above each sample refer to the specific transgenic line tested.…”
Section: A Cbf Cold-response Pathway In Brassica Napusmentioning
confidence: 99%
“…Total soluble protein (100 g) was fractionated by 10% (w/v) acrylamide tricine SDS/ PAGE (Schägger and von Jagow, 1987) and transferred to 0.1-m nitrocellulose membranes by electroblotting (Towbin et al, 1979) as described (Artus et al, 1996). BN28 protein was detected using antiserum kindly provided by Anne Johnson (Boothe et al, 1997) and visualized using the enhanced chemiluminescence system (Amersham, Buckinghamshire, UK).…”
Section: Immunoblot Analysismentioning
confidence: 99%
“…At decreasing temperature, intensity of NMR signals also decreases leading to the identification of intracellular freezing in the plant tissues. In Brassica, NMR was used to analyze the structure of low temperature-induced protein (Boothe et al 1997). NMR spectroscopy quantifies liquid water.…”
Section: Temperaturementioning
confidence: 99%